The saline water-soluble sticks with protective coating - L. A. Ivanova; Ju. G. Barinov; A. A. Bondar (Литьë и металлургия)
In the article there is shown the possibility of formation of metal coat from nickel-alluminum alloy on saline sticks with melting temperature about 300 degrees Celsius at keeping of certain technological techniques.